Liability of the Custodian or Custodian Body for the Damage Caused by the Persons Totally Divested from the Ability to Act Due to Mental Disability - Tahiri, Burim (European Scientific Journal, ESJ, 2017)
Liability of the custodian or custodian body for the damage caused by the persons totally divested from the ability to act due to mental disability is a kind of liability for the damage caused by the actions of the other person. In this case, his/her custodian or custodian body that is liable for his/her supervision shall be liable even for the damage caused by the person with mental disabilities. Obligation for supervision and care of the custodian or custodian body for the person with mental disabilities shall be the reason based on which they should respond in cases when the person with mental disabilities causes a damage to the third person. In order this kind of liability to come into consideration, in advance, there should be met some conditions as follows: 1. The damage is caused, 2. The damage is caused by the person that is incapable to judge and by the person who is under custody, 3. The damage has been caused since the custodian has not exercised adequately the supervision function as required according to the Law, decision of a body or any contract. These conditions should be fulfilled together in order that this kind of liability to come into consideration. Theoretical treatments regarding these kinds of liabilities, not in all cases, have brought the due clearance. In theoretical treatments of various authors that have treated this kind of liability there are presented dilemma which require a different analysis and approach in order that there to be identified some cases that have been left untreated until nowadays. Those authors, in their theoretical treatments, have ascertained that the custodian or custodian body shall be released from the liability for the damage caused by the person with mental disabilities or with mental slowdown development or any other circumstance according to which they could not judge his/her actions, if they can prove their innocence whether they have exercised adequately the supervision towards the person with mental disabilities or with mental slowdown development but the same authors have not given further explanations that who will be liable in such cases if the person with mental disabilities does not have economic conditions to make the compensation of the damage. This issue is regulated with legal framework of some countries treated in this paper. We have done this comparative analysis between the legal framework of these countries with the purpose of identifying the similarities and differences between them in regulating this liability. Even that there are some differences in legal determinations, we should say that Kosovo, Croatia, Serbia, Albania, France, Italy, Germany and Spain have approximately similar regulation regarding this liability since all these countries cover this kind of liability with their legal framework.